NF-κB signaling contributes to the inhibitory effects of Bombyx batryticatus on neuroinflammation caused by MPTP toxicity - Lim, Hye-Sun; Jang, Yumi; Moon, Byeong Cheol; Park, Gunhyuk (Bangladesh Journal of Pharmacology, 2021)
Bombyx batryticatus, the dried larvae of Bombyx mori infected by Beauveria bassiana, is a renowned traditional medicine. Previous report shows that B. batryticatus improved behavioral impairments, protected dopaminergic neurons, and maintained dopamine levels by inhibiting oxidative signaling in murine Parkinson’s disease model. In this study, the inhibitory effects of B. batryticatus on 1-methyl 4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease in mice was investigated and explored the corresponding molecular mechanisms, while focusing on NF-κB signaling. Consequently, it was found that B. batryticatus inhibited glial and microglial activation and the levels of neuroinflammatory mediators, such as Cox-2, iNOS, and NF-kB, in the substantia nigra pars compacta. Moreover, pre-inhibition of NF-κB by BAY 11-7082, a κB kinase inhibitor, could neutralize the inhibitory effects of B. batryticatus against the activation of glia and microglia formerly induced by MPTP. It can be considered that B. batryticatus holds implications in providing anti-inflammatory neuroprotection by regulating NF-κB signaling.